A Study on the Current Status of Integrating Jiangxi Red Culture into College English Curriculum From the Perspective of Cultural Confidence - Qin, Juanjuan (Pacific International Journal, 2025)
Effectively integrating Jiangxi Red Culture into College English curriculum to enhance students’ cultural confidence remains a critical task for advancing ideological and political education reform during the new era. Based on an analysis of the value implications of integrating Jiangxi red culture into college English courses, this study analyzes the current status of integrating Jiangxi red culture into College English curriculum, through empirical research methods such as questionnaire survey and interview. The findings reveal systemic deficiencies in red cultural cognition, teaching methods, extracurricular practice, and evaluation mechanisms, which collectively hinder the practical effectiveness of Jiangxi red culture integration within English higher education.